Development of brain mechanisms for processing affective touch - Bjornsdotter, Malin; Gordon, Ilanit; Pelphrey, Kevin A.; Olausson, Håkan; Kaiser, Martha (Frontiers in Behavioral Neuroscience, 2014)
Affective tactile stimulation plays a key role in the maturation of neural circuits, but the development of brain mechanisms processing touch is poorly understood. We therefore used functional magnetic resonance imaging (fMRI) to study brain responses to soft brush stroking of both glabrous (palm) and hairy (forearm) skin in healthy children (5-13 years), adolescents (14-17 years) and adults (25-35 years). Adult-defined regions-of-interests in the primary somatosensory cortex (SI), secondary somatosensory cortex (SII), insular cortex and right posterior superior temporal sulcus (pSTS) were significantly and similarly activated in all age groups. Whole-brain analyses revealed that responses in the ipsilateral SII were positively correlated with age in both genders, and that responses in bilateral regions near the pSTS correlated significantly and strongly with age in females but not in males. These results suggest that brain mechanisms associated with both sensory-discriminative and affective-motivational aspects of touch are largely established in school-aged children, and that there is a general continuing maturation of SII and a female-specific increase in pSTS sensitivity with age. Our work establishes a groundwork for future comparative studies of tactile processing in developmental disorders characterized by disrupted social perception such as autism.